Missive: Fast Appliance Launch From an Untrusted Buffer Cache - Howell, Jon; Elson, Jeremy; Parno, Bryan; Douceur, John (JD) (2013)
The rise of virtualization on servers and more secure application architectures on client systems (e.g., iOS, Android, Windows 8) has resulted in a multitude of systems in which strongly isolated applications from mutually distrusting vendors run atop a minimal layer of host software. As functionality migrates out of the trusted computing base and into applications, how can we provide fast, interactive application launch times without relying on a trusted buffer cache? This paper presents Missive, an end-to-end system for generating application image files, transmitting them across the wide-area Internet, and storing them in an untrusted cache. Via an architecture that is carefully designed to exploit application commonality, Missive preserves the abstraction of purely isolated app launch and yet launches apps in only a few hundred milliseconds.